2013
DOI: 10.1155/2013/879845
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Mitigates Cisplatin-Induced Nephrotoxicity by Regulating CD4+CD25+Foxp3+Regulatory T Cells in Mice

Abstract: Cisplatin is used as a potent anticancer drug, but it often causes nephrotoxicity. Bee venom (BV) has been used for the treatment of various inflammatory diseases, and its renoprotective action was shown in NZB/W mice. However, little is known about whether BV has beneficial effects on cisplatin-induced nephrotoxicity and how such effects might be mediated. In the present study, the BV-injected group showed a significant increase in the population of Tregs in spleen. Although there was no significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Our recent study demonstrated that BV causes immune tolerance by increasing the population of CD4 þ CD25 þ Foxp3 þ Tregs in lupus nephritis, cisplatininduced nephrotoxicity, and an allergic asthma model [26][27][28]. In the present study, we investigated whether bvPLA2 induces immunosuppressive effects that are mediated via Treg cells in an OVA-induced allergic asthma model.…”
Section: Introductionmentioning
confidence: 92%
“…Our recent study demonstrated that BV causes immune tolerance by increasing the population of CD4 þ CD25 þ Foxp3 þ Tregs in lupus nephritis, cisplatininduced nephrotoxicity, and an allergic asthma model [26][27][28]. In the present study, we investigated whether bvPLA2 induces immunosuppressive effects that are mediated via Treg cells in an OVA-induced allergic asthma model.…”
Section: Introductionmentioning
confidence: 92%
“…42 Although the relative contributions of Treg enhancement and leukocyte sequestration for protection against IRI are debatable, PC61 pretreatment negated the protection induced by FTY720, and Treg adoptive transfer into PC61-and FTY720-treated mice restored the protective effect of FTY720. 42 Recently, Kim et al 43 reported that bee venom increases Treg numbers in the spleen, enhances Treg trafficking to the kidney after cisplatin administration, and protects against cisplatin-induced kidney injury in mice. Importantly, bee venom had no adverse effects on the antitumor activity of cisplatin in the model by Kim et al 43 There are numerous other pharmacological agents that have been shown to boost Treg numbers or function in vivo (examples in Table 1).…”
Section: Targeting Of Intrinsic Tregsmentioning
confidence: 99%
“…42 Recently, Kim et al 43 reported that bee venom increases Treg numbers in the spleen, enhances Treg trafficking to the kidney after cisplatin administration, and protects against cisplatin-induced kidney injury in mice. Importantly, bee venom had no adverse effects on the antitumor activity of cisplatin in the model by Kim et al 43 There are numerous other pharmacological agents that have been shown to boost Treg numbers or function in vivo (examples in Table 1). These studies suggest that pharmacologically targeting intrinsic Tregs in humans may be a promising therapeutic option for AKI.…”
Section: Targeting Of Intrinsic Tregsmentioning
confidence: 99%
“…As in other disease models, a variety of interventions have been linked to enhance Treg number or function in cisplatin nephrotoxicity. Interestingly, bee venom injections, with the active component being phospholipase A2 (PLA2), a calcium‐dependent lipolytic enzyme before the administration of cisplatin increase Treg numbers in the spleen and enhance their recruitment during the early phase of cisplatin‐induced nephrotoxicity, reducing renal dysfunction and intrarenal inflammation, accompanied by reduced intrarenal IL‐6 and TNF . The effects of PLA2 were dependent on the presence of Tregs, and mediated through binding to mannose receptor CD206 on dendritic cells, inducing IL‐10 production .…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Interestingly, bee venom injections, with the active component being phospholipase A2 (PLA2), a calcium-dependent lipolytic enzyme before the administration of cisplatin increase Treg numbers in the spleen and enhance their recruitment during the early phase of cisplatin-induced nephrotoxicity, reducing renal dysfunction and intrarenal inflammation, accompanied by reduced intrarenal IL-6 and TNF. 85,86 The effects of PLA2 were dependent on the presence of Tregs, and mediated through binding to mannose receptor CD206 on dendritic cells, inducing IL-10 production. 86 The renoprotective effects of human-umbilical cord blood-derived MSCs administered early after cisplatin administration are potentially via Tregs.…”
Section: Cisplatin Nephrotoxicitymentioning
confidence: 99%